Optimized Cingulate Island Sign in Discriminating Dementia With Lewy Bodies From Alzheimer Disease. (22nd May 2023) - Ge, Jingjie; Lin, Huamei; Chen, Keliang; Wang, Min; He, Zhijie; Lu, Jiaying; Ju, Zizhao; Sun, Yimin; Liu, Fengtao; Guan, Yihui; Zhao, Qianhua; Zuo, Chuantao; et al.
Abstract : Purpose: This study aimed to optimize the analysis of cingulate island sign (CIS) to improve its diagnostic accuracy in discriminating dementia with Lewy bodies (DLB) from Alzheimer disease (AD). Patients and Methods: Patients with DLB (n = 80), AD (n = 75), and normal controls (n = 22) with 18 F-FDG PET imaging were enrolled in this study. Sixty-two DLB patients also underwent dopaminergic PET scans. The optimized/conventional CIS ratios and metabolism in associated brain regions were evaluated by diagnostic accuracy among groups and correlation with cognitive/dopaminergic dysfunction. Results: In discriminating DLB from AD, the optimized CIS ratio calculated by dorsal posterior cingulate cortex (PCC)/lateral occipital lobe metabolism achieved the highest specificity, sensitivity, and accuracy at 0.907, 0.750, and 0.825, respectively. The metabolism of dorsal-PCC positively correlated with cognitive impairment in DLB patients cross-sectionally and longitudinally ( P < 0.001, r = 0.601; P = 0.044, r = 0.645), and also correlated with dopaminergic impairment in the caudate ( P = 0.048, r = 0.315). Conclusions: Optimized CIS ratios of incorporated metabolic activity of dorsal-PCC and occipital subregions are clinically useful for differentiating DLB from AD, in which dorsal-PCC metabolism may provide an objective biomarker to reflect the severity of cognitive impairment in DLB.